Viva voce presentation DBA UiTM Shah Alam : Nur Azlina Mohd Isa - UiTM, Arshad Ayub Graduate Business School (Arshad Ayub Graduate Business School, 2020)
Project and Operational Stakeholders Perspectives of an Airport Terminal Project Outcome